Análise estatística da OBMEP em MT sob a ótica dos descritores da Prova Brasil - Santos, Paulo dos (2018)
We present in this work a study where we make a relationship between the questions of the 2nd phase, level 2 tests of the OBMEP-Brazilian Mathematics Olympiad of the Public Schools of the years 2014, 2015 and 2016 with the themes and descriptors of the Reference Matrix of the Proof Brazil. Initially we contextualize the OBEMP and Prova Brasil and relate each of the OBMEP issues to the themes and descriptors addressed. We also present a mapping of the municipalities of Mato Grosso and a statistical analysis of the performance of the students of these municipalities, comparing the scores of the two evaluations.